Teacher's Strategy in Forming Student Character at SMP Santa Maria Maumere - Jon, Siprianus; Gleko, Gabriel; Nuwa, Gisela (Lembaga Riset Mutiara Akbar, 2023)
The teacher is one of the components of the educational process in shaping the disciplinary character of students. because the teacher is in direct contact with the learning process. One of the factors in character formation is exemplary, including: discipline, speech, attitude, honesty, is a strategy in character building. The formation of character is very important for students to have a good personality. The teacher's strategy in shaping the character of students through integration strategies which include; integration through daily activities in the form of giving exemplary examples such as reprimands, advice, environmental conditioning that supports character education, routine activities, character refraction, and companion activities and supervision of character education. One of the teacher's ways or strategies so that the character of students is better is carried out through intracurricular and extracurricular activities, through demonstration activities and direct application, through the preparation of interesting learning plans and tools and the teacher must protect one another. Efforts made by the teacher in shaping the character of students through learning activities in schools conducting coaching for students, the teacher as a media, the teacher evaluates and instills honest values and responsibility for student character. The research method used is a qualitative approach. The data sources in this study are primary data sources and secondary data sources. The informants selected in this study were school principals and teachers. Data collection techniques used are observation techniques, interviews and documentation. Data analysis techniques consist of data collection, data reduction, drawing conclusions or verification.